2008
DOI: 10.5465/amr.2008.32465769
|View full text |Cite
|
Sign up to set email alerts
|

Ending Corruption: The Interplay Among Institutional Logics, Resources, and Institutional Entrepreneurs

Abstract: We draw from theories of institutions and collective identities to present a threefold framework of institutional change-involving institutional logics, resources, and social actors-that furthers our understanding of the mitigation of corruption. Those social actors intent on reforming corruption function as institutional entrepreneurs, and their success depends both on articulating an anticorruption institutional logic that incorporates corruption-disabling identities, cognitive schemas, and practices and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
321
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(333 citation statements)
references
References 67 publications
5
321
2
5
Order By: Relevance
“…For example, it was a common aphorism in many socialist countries the "those who do not steal from the state steal from their families" (Misangyi et al 2008). Such general "Robin Hood" attitudes still exist in the postcommunist period and makes 'stealing back' from the state perfectly legitimate or even obligatory for major part of society (Jancsics 2015).…”
Section: Similarities Between Gifts and Bribesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was a common aphorism in many socialist countries the "those who do not steal from the state steal from their families" (Misangyi et al 2008). Such general "Robin Hood" attitudes still exist in the postcommunist period and makes 'stealing back' from the state perfectly legitimate or even obligatory for major part of society (Jancsics 2015).…”
Section: Similarities Between Gifts and Bribesmentioning
confidence: 99%
“…Crossing the line between bureaucratic gift and bribe is often authorized by managers (Misangyi et al 2008). Here the formal organizational rule bans the exchange while informal norms legitimated by authorities allow it.…”
Section: Bribery As Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Capturing this relationship directly, Misangyi, Weaver, and Elms (2008: 754) note that, "institutions provide the shared meaning that gives coherence to social life through the creation of social identities… that define the cognitive schemas and roles governing behavior in a given situation." Offering an illustration, Lok (2010) showed that the manager identity in the United Kingdom is tied to a commercial logic and carries behavioral expectations related to profit-maximization.…”
Section: Identity Logics and Social Enterprisementioning
confidence: 99%
“…Our focus on corruption control also ties in with the growing interest among scholars of management, organization, communication and international business studies in exploring corruption and corruption control mechanisms at the firm or industry levels. This includes a focus on the relationship between corruption control in organizations and the wider corporate social responsibility agenda [4,37,40,44]; between forms of hidden or anonymous organizing [52] and the project of accountability and transparency so characteristic of our times [19,31,32]; and, not least, between corruption and aspirations of moral learning and education at universities and business schools [54,56].…”
Section: Corruption and Its Public Enemies: Investigating Changing Rementioning
confidence: 99%